Assessment for learning practices among Malay language teachers in Malaysia National Type Chinese School - Oya, Siti Aishah Wan; Nordin, Zaimuariffudin Shukri (Institute of Advanced Engineering and Science, 2025)
This study investigates the issues Malay language teachers in Malaysia National Types Chinese School (SJKC) regarding the inconsistent application assessment for learning (AfL) practices, the persistence of traditional teachercentered, and the challenge of aligning AfL practices with curriculum standards and assessment criteria. These issues have a critical impact on the effectiveness of assessment, teaching, and learning. Given AfL’s potential to address educational challenges and enhance student outcomes, this study is highly relevant. To achieve this goal, a qualitative case study design approach, six participants were selected using the following criteria in purposive sampling, using data gathered from in-depth semi-structured interviews, informal conversations, lesson plans and assessment methods. Thematic analysis conducted using Atlas.ti, revealed three main themes: knowledge of AfL, AfL practice, and obstacles and challenges. The results show that most teachers primarily use belief AfL to improve student outcomes, but there are significant differences between beliefs and practices. Moreover, lack of knowledge which poses challenges due to shifts in curriculum standards and assessment administration in school. Given the results, suggestions embedding AfL principle into AfL practices to develop an objective framework for AfL and tracking second language learners’ language proficiency and progress, improving learning outcomes and language acquisition.